Effects of ageing on orofacial fine force control and its relationship with parallel change in sensory perception. - ETTER, NICOLE M.; MCKEON, PATRICK O.; DRESSLER, EMILY V.; ANDREATTA, RICHARD D. (International Journal of Speech-Language Pathology, 2018)
Purpose: Current theoretical models suggest the importance of a bidirectional relationship between sensation and production in the vocal tract to maintain lifelong speech skills. The purpose of this study was to assess age-related changes in orofacial skilled force production and to begin defining the orofacial perception-action relationship in healthy adults. Method: Low-level orofacial force control measures (reaction time, rise time, peak force, mean hold force (N) and force hold SD) were collected from 60 adults (19-84 years). Non-parametric Kruskal Wallis tests were performed to identify statistical differences between force and group demographics. Non-parametric Spearman’s rank correlations were completed to compare force measures against previously published sensory data from the same cohort of participants. Result: Significant group differences in force control were found for age, sex, speech usage and smoking status. Significant correlational relationships were identified between labial vibrotactile thresholds and several low-level force control measures collected during step and ramp-and-hold conditions. Conclusion: These findings demonstrate age-related alterations in orofacial force production. Furthermore, correlational analysis suggests as vibrotactile detection thresholds increase, the ability to maintain low-level force control accuracy decreases. Possible clinical applications and treatment consequences of these findings for speech disorders in the ageing population are provided.